2014
DOI: 10.1109/ted.2014.2364781
|View full text |Cite
|
Sign up to set email alerts
|

A Surface-Field-Based Model for Nanowire MOSFETs With Spatial Variations of Doping Profiles

Abstract: We report a novel method to solve the nonlinear 1-D Poisson's equation for the gate-all-around (GAA) nanowire MOSFETs with nonuniform doping profiles. An algebraic relation between the electric field and potential is identified to develop a surface-field-based compact model. Drain current is derived from the oxide-interface boundary condition to avoid the complicated surface-potential approach. As verified by the TCAD simulations, this analytic model is capable of continuously covering all operating regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Surrounding-gate MOSFETs (SRGMOSFETs) has been widely studied as the structure of logic devices to replace the conventional planar MOSFETs in improving the control over the short-channel effects [1][2][3][4]. For more than a decade, SRGMOSFET compact modeling has been an active research area and various types of compact models were reported [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In its early development, the compact models were obtained for the undoped case by solving the one-dimensional (1D) Poisson's equation that contains only the mobile-charge term [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surrounding-gate MOSFETs (SRGMOSFETs) has been widely studied as the structure of logic devices to replace the conventional planar MOSFETs in improving the control over the short-channel effects [1][2][3][4]. For more than a decade, SRGMOSFET compact modeling has been an active research area and various types of compact models were reported [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In its early development, the compact models were obtained for the undoped case by solving the one-dimensional (1D) Poisson's equation that contains only the mobile-charge term [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, SRGMOSFET compact modeling has been an active research area and various types of compact models were reported [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In its early development, the compact models were obtained for the undoped case by solving the one-dimensional (1D) Poisson's equation that contains only the mobile-charge term [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, due to the unintentional doping, the highly-doped body of SRGMOSFET has resulted in an increase of its threshold voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Device performance with miniaturization is the vital goal of the microelectronics community. Cylindrical gate all around (CGAA) MOSFET with the reduced gate length of 22 nm is an ultimate solution [1][2][3] . CGAA provides excellent electrostatic gate control over the channel and drastically reduces short channel effects (SCEs) and hot carriers effects (HCEs) [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MOSFET dimensions has drastically reduced approaching to nanoscale regime with steeply increased short channels effects [1][2][3][4]. At nanoscale the junction depletion width (p-n) at SourceChannel (S-C) and Channel-Drain (C-D) junctions can not be neglected as it degrades the ON current due to increased S-C and C-D resistance [5][6][7][8] and is actively involved in MOSFET device performance.…”
Section: Introductionmentioning
confidence: 99%